Integral Equations Approach in Complex-Valued Generalized b-Metric Spaces - Shahid Mehmood; Saif Ur Rehman; Ihsan Ullah; Rashad A. R. Bantan; Mohammed Elgarhy (Journal of Mathematics)
In this paper, we study a rational type common fixed-point theorem (CFP theorem) in complex-valued generalized b-metric spaces (Gb-metric spaces) by using three self-mappings under the generalized contraction conditions. We find CFP and prove its uniqueness. To justify our result, we provide an illustrative example. Furthermore, we present a supportive application of the three Urysohn type integral equations (UTIEs) for the validity of our result. The UTIEs are